2020
DOI: 10.2298/vsp180629155k
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of age-related influences on the quality of life of breast cancer patients before and after surgical treatment

Abstract: Background / Aim. Breast cancer comprises about 25% of all female cancers, and its incidence is increasing. New diagnostic procedures and therapeutic modalities have increased treatment success rates as well as patient survival. The goal of contemporary treatment is not only patient survival, but also a better quality of life (QoL). The objective of this study was to assess the effect of age at diagnosis on the QoL of a patient with breast cancer before and after surgery. Methods. We analyzed QoL in 170 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In this study, the results showed that hair loss decreased during follow-up 1 year after the end of chemotherapy. In our research, most women were treated with chemotherapy (63.7%) which led to a higher rate of psychosexual disorders due on the scales of self-image, sexual functioning, sexual pleasure, side effects of systemic therapy, and anxiety due to hair loss, which is consistent with the results of other studies [21], [22], [23], [24]. The results of a study conducted by Murgic et al in Croatia showed that the self-image scale was the most affected, while sexual functioning was minimally affected, which is contrary to our research [25].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the results showed that hair loss decreased during follow-up 1 year after the end of chemotherapy. In our research, most women were treated with chemotherapy (63.7%) which led to a higher rate of psychosexual disorders due on the scales of self-image, sexual functioning, sexual pleasure, side effects of systemic therapy, and anxiety due to hair loss, which is consistent with the results of other studies [21], [22], [23], [24]. The results of a study conducted by Murgic et al in Croatia showed that the self-image scale was the most affected, while sexual functioning was minimally affected, which is contrary to our research [25].…”
Section: Discussionsupporting
confidence: 92%
“…The p-value between the two types of chemotherapy at the end of treatment at p = 000.027 - this is the only time point that is significant. Kostic et al (2020) [ 76 ] Serbia 170 n = 43 < 50, n = 127 ≥ 50 EORTC QLQ-C30 a Mean (SD a ): physical functioning pre-surgery <50 years 90.3 (11.4), ≥50 years 83.7 (18.8) (p = 0.103) (not significant). Post-surgery age differences also not significant, <50 years 81.2 (16.7), ≥50 years 76.5 (18.7) (p = 0.134).…”
Section: Resultsmentioning
confidence: 99%
“…The range of scores was 17–24, with a mean of 20.3 ( Appendix B ). Six studies (13.6 %) had scores at the optimum end of the scale, with scores of 23–24 [ 56 , 58 , [71] , [73] , [74] , 84 ], and ten (22.7 %) were amongst the lower end of the range, with scores of 17–18 [ 53 , 72 , 59 , 60 , 67 , 76 , 77 , 79 , 91 , 93 ]. Studies scored poorly on aspects about confounding variables, the generalisability to the local population and follow-up period [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 170 female breast cancer patients 1 month before and after surgical treatment, there are statistically significant differences in the QoL domains of sexual functioning and sexual enjoyment between younger and older women independently of surgery [19], [20]. The surgical treatment negatively affects the QoL independently of age.…”
Section: Discussionmentioning
confidence: 99%